A role of IL-1R1 signaling in the differentiation of Th17 cells and the development of autoimmune diseases - Sha, Yonggang (Landes Bioscience, 2011)
IL-1 cytokine family plays a key role in the innate immune response against pathogen- and danger-associated molecular patterns. More recently, IL-1 receptor type 1 (IL-R1) signaling has been identified as a critical step in the differentiation and commitment of Th17 cells, which mediate the development of autoimmune diseases. Given its significance in the induction of the adoptive immune response, this complex signaling pathway is tightly regulated. Upon binding of IL-1 to IL-1R1, IL-1R accessory protein (AcP) is recruited to form a high affinity IL-1R1-IL-1RAcP heterodimeric receptor, which initiates the downstream signaling cascade. Multiple negative regulators of this pathway, including inhibitory membrane-bound IL-RII, secreted soluble (s)IL-1RI, sIL-RII and sIL-1RAcP, the regulatory IL-1R1 antagonist (IL-1R1a) and the IL-1R1-signlaing-induced single Ig-IL-1R-related (SIGIRR), provide a negative feedback control of this pathway, and suppress excessive IL-1 signaling and Th17 cell differentiation. IL-1R1 signaling induces human Th17 cell differentiation, leading to the expression of IL-1R-associated protein kinase (IRAK)4 and retinoic acid-related orphan nuclear hormone receptor (ROR), Th17 cell lineage transcription factors, which together with signal transducer and activator of the transcription (STAT)3, activate this cell lineage's specific cytokine expression profile, including IL-17A, IL-17F, IL-21 and IL-22. Given the role of IL-1 signaling and Th17 cells in the development of the autoinflammatory and autoimmune diseases, therapeutic strategies inhibiting IL-1R1 signaling are discussed as a novel approach for the treatment of autoimmune diseases and particularly multiple sclerosis (MS).